Review of Kateřina Králová, Konstantinos Tsivos et al., Vyschly Nám Slzy... Řečtí uprchlíci v Československu [We have no tears left to cry: Greek refugees in Czechoslovakia] - Sarikoudi, Georgia (Historein, 2014)
Kateřina Králová, Konstantinos Tsivos et al., Vyschly Nám Slzy... Řečtí uprchlíci v Československu [We have no tears left to cry: Greek refugees in Czechoslovakia], Prague: Dokořán. 2012. 333 pp.